Preclinical Antileukemia Activity of Tramesan: A Newly Identified Bioactive Fungal Metabolite. (15th November 2017) - Ricciardi, M. R.; Licchetta, R.; Mirabilii, S.; Scarpari, M.; Parroni, A.; Fabbri, A. A.; Cescutti, P.; Reverberi, M.; Fanelli, C.; Tafuri, A.
Abstract : Despite improvements that occurred in the last decades in the acute myeloid leukemia (AML) treatment, clinical results are still unsatisfactory. More effective therapies are required, and innovative approaches are ongoing, including the discovery of novel antileukemia natural compounds. Several studies have described the activity of extracts from mushrooms which produce compounds that exhibited immunological and antitumor activities. The latter has been demonstrated to be promoted in vitro by mushroom polysaccharides via induction of apoptosis. However, the antileukemia activity of these compounds on primary cells is still not reported. In the present study, we examined the in vitro effects of Tramesan (TR), a bioactive compound extracted from Trametes versicolor, on leukemic cell lines and primary cells. Our results demonstrated that TR induced a marked growth inhibition of leukemic cell lines and primary cells from AML patients. The antiproliferative effects of TR were associated in primary AML cells with a significant increase of apoptosis. No significant cytotoxic effects were observed in normal peripheral blood mononuclear cells (MNC) from healthy donors. Our data demonstrated a cytotoxic activity of TR on leukemia cells prompting further translational applications. Ongoing studies are elucidating the molecular mechanisms underlying its antileukemic activity.